2021
DOI: 10.1177/10775595211001109
|View full text |Cite
|
Sign up to set email alerts
|

Reasonable Efforts? Child Maltreatment Investigations and Service Referrals of Parents With Ascribed Cognitive Impairments in Canada

Abstract: Parents with ascribed cognitive impairment (CI) are more likely than parents without CI to have their children removed by child protective services (CPS). Inequitable access to parenting and family supports and services is thought to be a contributing factor. Utilizing data on a 3-month sample of 15,980 child maltreatment investigations across Canada, including 1,244 cases featuring parents with CI, this study investigated service referrals and non-referrals. The results of this secondary data analysis suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The highest estimate was reported in the large clinical-sample study by Hellfritz (2018), which employed an operationalization that included both prolonged out-of-home placements and repeated moves between caregivers. Pacheco et al (2021) reported an almost identical estimate in their large court-based study, with just above 35% of parents with ID having childhood experiences of out-of-home placement, compared to 10% of the parents without ID. Gillberg and Geijer-Karlsson (1983) also reported a very similar estimate in a small clinical sample, with 34% of the mothers with ID having been partly or wholly raised in institutions.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The highest estimate was reported in the large clinical-sample study by Hellfritz (2018), which employed an operationalization that included both prolonged out-of-home placements and repeated moves between caregivers. Pacheco et al (2021) reported an almost identical estimate in their large court-based study, with just above 35% of parents with ID having childhood experiences of out-of-home placement, compared to 10% of the parents without ID. Gillberg and Geijer-Karlsson (1983) also reported a very similar estimate in a small clinical sample, with 34% of the mothers with ID having been partly or wholly raised in institutions.…”
Section: Resultsmentioning
confidence: 94%
“…Third, negative conceptions about the caregiving capacity of parents with ID are widespread (for a discussion, see e.g., Höglund et al, 2013), while the potential relevance of IPT for understanding their challenges is often overlooked (e.g., Mevissen et al, 2020). More solid knowledge about the role of IPT for caregiving-relevant and child outcomes in these families could contextualize caregiving difficulties and, thereby, counteract essentializing tendencies and discriminatory practices (Pacheco et al, 2021).…”
mentioning
confidence: 99%
“…were not referred to suitable parenting programs and either received instruction from the protection worker or were referred to a community-based program that was unlikely to be effective for parents with intellectual disabilities. This lack of knowledge regarding appropriate service referrals and lack of inclusive services, has also been demonstrated in previous research (Pacheco et al, 2022) and must be addressed to avoid future scenarios in which the fate of a family is at risk when specialised resources could allow the family to stay together (Adolfsson et al, 2021).…”
Section: 'Cherry-picking' Of Evidence-based Practicesmentioning
confidence: 89%
“…children have a prolonged involvement with CPS and have an increased risk of out-of-home placement (e.g., Buchan & Gunn, 2007;McConnell et al, 2011aMcConnell et al, , 2011bMcConnell et al, , 2021Pacheco et al, 2021;Willems et al, 2007).…”
Section: Introductionmentioning
confidence: 99%